SOSIALISASI KESANTUNAN BERBAHASA DALAM PENGGUNAAN SOSIAL MEDIA DI KALANGAN SISWA SMP NEGERI 8 TANGERANG SELATAN - Yasir Mubarok; Adam Muhammad Nur; Eris Risnawati; Washadi W. (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2019)
This activity aims to help SMP Negeri 8 Tangerang Selatan that has the desire to shape the character of its students in aspect of language use. Nowadays, many cases of the impolite language in social media make a quite bad impact to its users. One effect that can be seen immediately is that the users can get into a trouble because of the language that they use. The use of this impolite language occurs because there is a lack of awareness of social media users about patterns of language politeness and the negative impacts that occur when the practice of language impoliteness is done, especially for users at an early age, so that the activities carried out are aimed at stimulating media users social especially young social media users so that they are aware of how to use polite language on social media properly and correctly. The hope to be achieved is the completion of this activity the students at SMP Negeri 8 Tangerang Selatan can apply polite language when using social media and avoid using inappropriate language so that they avoid legal issues, especially if the use of this impolite language used for harassment or insulting others, so students can sort and think when they will comment or write something on their social media.